Google in informacijski viri za področje bibliotekarstva in informacijske znanosti - Sluga, Marjetka (Knjižnica, 2007)
The article is based on the author's (Sluga, 2006) research which was the basis for her bachelor's thesis. The purpose of the research was to analyse and compare the performance of different online based information retrieval systems in answering queries on library and information science. A case study approach which included four carefully selected cases was used. Search was made in Google, Google Scholar and in appropriate library databases and systems. The performance of these systems was assessed in terms of relevancy, uniqueness, quality, accessibility of documents and precision. The findings demonstrate the advantages and disadvantages of each type. Library databases were highly successful in relevancy, quality and uniqueness of the results and have the ability to retrieve a more precise set of documents. With Google, there were no problems with accessibility, and it offers a high proportion of unique documents. Google Scholar is superior in quality but there are more problems with accessibility. Thus, these systems complement each other.
Keywords: iskanje informacij; informacijski viri; spletne strani; iskalniki; knjižnice; library science; bibliotekarstvo; Google Scholar